Recombinant Zika virus envelope protein elicited protective immunity against Zika virus in immunocompetent mice - Liang, Huabin (PLoS One, 2018)
Zika virus (ZIKV) has caused great public concerns due to its recent large outbreaks and a close association with microcephaly in fetus and Guillain-Barre syndrome in adults. Rapid development of vaccines against ZIKV is a public health priority. To this end, we have constructed and purified recombinant ZIKV envelope protein using both prokaryotic and eukaryotic expression systems, and then tested their immunogenicity and protective efficacy in immune competent mice. Both protein immunogens elicited humoral and cellular immune responses, and protected immune competent mice from ZIKV challenge in vivo. These products could be further evaluated either as stand-alone vaccine candidate, or used in a prime-and-boost regimen with other forms of ZIKV vaccine.